Rāmakṛṣṇa Paramahaṁsa : A Psychological Profile - Sil, Narasingha P. (Asian Studies - Book Archive pre-2000., 1991)
In the entire corpus of Rāmakṛṣṇa research, carried out mostly by his disciples, devotes, and admirers, only a handful have attempted to analyze his divine reputation. Yet none has examined the Rāmakṛṣṇa phenomenon fully. This is the first comprehensive psychoanalysis of Rāmakṛṣṇa's sexuality in general and his androgyny in particular, as well as a critical examination of his sermons samādhis . Instead of the popular paramahaṁsa there now emerges the less attractive but more authentic profile of an utterly selfish, capricious but highly intelligent spiritual master who elicited awed submission from everybody by his unpredictable and frenzied behaviour. The author asserts that Rāmakṛṣṇa's spiritual odyssey is better explained as his desperate but successful effort to deal with his emotional and sexual crisis, rather than as the universally acknowledged outcome of a divine teleology. Attempting to distinguish the historical Rāmakṛsṇa from the godhead of hagiography, this study offers a challenging debate on mystic phenomenon.